ANALISIS PENGARUH KUALITAS WEBSITE DAN KEPERCAYAAN TERHADAP KEPUASAN PELANGGAN DALAM MEMBENTUK MINAT PEMBELIAN ULANG PADA PENGGUNA LAZADA DI PEKANBARU - Prayogi.S Hari; Restuti Sri; Sari Novia Henni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
The development of information technology currently has a positive impact on the growth of business activities in Indonesia. The increasing number of internet users provides opportunities for businesses to gain a large profit by opening an online store business. This makes changes in the way of shopping done by some people, in this era digital Businesses certainly need to pay attention to the quality of the website and build the trust given by the platform to see the influence of the website is able to provide satisfaction to consumers. This research aims to find out the influence of website quality and trust in customer satisfaction in shaping repurchase Intention in Lazada users in Pekanbaru. This research uses a quantitative approach. The sample in this study was 160 people who had shopped at Lazada at least 2 times, domiciled in Pekanbaru and aged 17 years above. Sampling using non-probability sampling method and purposive sampling technique. This research instrument uses questionnaires and analyzed by path analysis with SPSS version 21 software as the application. The results showed that Website Quality and Trust had a significant effect on Customer Satisfaction. Website Quality and Trust Variables also had a significant effect on Re-Purchase Intentions directly and through Satisfaction, as well as Satisfaction has a significant effect on Re-Purchase Intention.Keywords : Website Quality, Trust, Satisfaction, Re-Purchase Intention, Lazada.